Pengaruh Return On Equity, Earning Per Share, dan Debt to Equity Ratio Terhadap Return Saham (Studi Pada Emiten Saham Syariah Sektor Properti dan Real Estate Yang Terdaftar di ISSI Tahun (2013-2015) - Nadia Amalia Latifah; Nisful Laila (Universitas Airlangga, 2017)
Islamic stocks is one of the most preffered investment type by Muslim investors. In the decision making process, the investors have to consider the financial reports and stock analysis. This research aim to investigate the effect of fundamental performance toward stock return property and real estate registered in ISSI in 2013 - 2015. Dependent variable is stock return and the independent variable are Return on Equity, Earning per Share, and Debt to Equity Ratio.The research used quantitative approach using secondary data. This research used panel data regression method.This research collecting data from the annual report from 2013 to 2015. This research used a significance level of 5%.Based on the regression analysis result, it indicate that ROE does not have significant effect to the stock returns. EPS and DER have significant effect to the stock returns. Simultaneously, ROE, EPS and DER have significant effect to the stock returns.